Adverse Events and Malpractice Claims in Endodontics (International Journal of Medical and Surgical Sciences, 2015)
An "adverse event" has defined as a non-intentional complication result of health care treatment, and although it can have different causes, always involves the providing care, but not the complications inherent to the patient’s disease itself. Adverse events, iatrogenic complications and malpractice have been clearly differentiated because only malpractice causes liability: while iatrogenic events can be result of a well-performed procedure, malpractice involves damage caused by negligence or lack of knowledge, and it is a potential for complaint and liability claim. In dentistry, endodontics is one of the specialties of greatest challenge where adverse events and malpractice claims have been reported with significant frequency. We present a literature review searching the main causes and results of malpractice claims in endodontics. Three articles from Italy, Israel and Denmark were selected, where the most claimed adverse events were root perforations, inappropriate drug therapies, defective root fillings and instrument fracture. One of the articles referred to malpractice verdicts in 97.5 % of claims. Since endodontics leads dental malpractice claims in Chile, strategies of risk management for these procedures are discussed; the adherence to strict protocols is proposed and measures to minimize the negative effects of these events are recommended.
Keywords: Endodontics; Malpractice; Adverse events